Synthesis and Cytotoxic Activity of a New Family of α-Hydroxyphosphonates with the Benzothiophene Scaffold - Mátyás Milen; Tamás Miklós John; Anna Sára Kis; Zsófia Garádi; Zsuzsanna Szalai; Angéla Takács; László Kőhidai; Konstantin Karaghiosoff; György Keglevich (Pharmaceuticals)
Background: α-Hydroxyphosphonates, one of the most prominent classes of phosphonates, remain of utmost importance because of their potential and real biological activity as pharmaceutical or pesticide agents. The effect is the consequence of their enzyme inhibitory properties. Objectives: It was planned to make available new heterocyclic hydroxyphosphonate derivatives with cytotoxic activity. Methods: After optimizing the synthesis, 23 members of a new family, α-hydroxy-α-(benzothiophen-2-yl)-methylphosphonates, were prepared by the Pudovik reaction of benzo[b]thiophene-2-carboxaldehydes and diethyl phosphite. The addition was performed at 26 °C in the presence of triethylamine as the catalyst. One of the products was also characterized by single-crystal X-ray analysis. Results: The cytotoxic effect of the α-hydroxy-α-benzothiophenyl-methylphosphonates was tested on U266 myeloma, A2058 melanoma, HT-29 colon, and EBC-1 lung cancer cell lines. Most of the molecules showed significant activity; the greatest effects were seen after treatment with hydroxyphosphonates with a trifluoromethyl group in the benzene ring. Conclusions: The cytotoxic activity of the newly synthesized α-hydroxyphosphonates is encouraging to find even better derivatives.